Daya Ledak Otot Lengan Terhadap Kemampuan Gyaku Zuki Dalam Kumite Karate-Ka Dojo Tiger Karate Camp Kota Padang - Risma Febriani; *Arie Asnaldi; Deswandi Deswandi; zulman zulman (Ilmu Olahraga, 2023)
The purpose of this study was to find out how much the relationship between the explosive power of the arm muscles and the ability of karateka to perform the gyaku zuki dojo Tiger Karate Camp in Padang City. This type of research is correlational with the population, namely karateka dojo Tiger Karate Camp, totaling 40 people. Sampling using purposive sampling, amounting to 23 male karateka. The data was taken by measuring the explosive power of the arm muscles and the ability of the gyaku zuki. The data obtained were analyzed by product moment and multiple correlations, and continued with the contribution with the determinant formula. Based on the data analysis it was found that there was a contribution of the explosive power of the arm muscles to the gyaku zuki's ability of 33.17%.